2015
DOI: 10.5539/ibr.v8n7p1
|View full text |Cite
|
Sign up to set email alerts
|

Noise, Uncertainty and Investor Psychology: A Behavioral Analysis

Abstract: The aim of this paper is to focus the interest on the behavioral finance contribution that helps understanding the financial market volatility. In order to put in evidence such an eventual GARCH effect between the exchange volume and the volatility of stock prices on Tunisian financial market. We borrowed the approach of Moschetto (1998) and Najand and Yung (1991) allowing the assessment of the GARCH (1, 1) Model. The data set consists of weekly stock prices and transaction volume. The sample period runs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Simonsohn and Ariely [92] suggested 13 that the basis of rational herding is the ability of observers to make unbiased inferences from the decisions they observe. However, people can be irrational [33,44,75]. Simonsohn and Ariely [92] suggested that irrational herding occurs when consumers (in our context, lenders) simply mimic others without rationally processing their observations of others' decisions.…”
Section: Rationality In Herdingmentioning
confidence: 87%
“…Simonsohn and Ariely [92] suggested 13 that the basis of rational herding is the ability of observers to make unbiased inferences from the decisions they observe. However, people can be irrational [33,44,75]. Simonsohn and Ariely [92] suggested that irrational herding occurs when consumers (in our context, lenders) simply mimic others without rationally processing their observations of others' decisions.…”
Section: Rationality In Herdingmentioning
confidence: 87%